Martin Wong: Human Instamatic - Corinna Kirsch (Panorama, 2016)

(untitled)
Martin Wong: Human Instamatic, the Bronx Museum’s ambitious exhibition of Martin Wong’s paintings, Cover of Martin Wong: Human Instamatic and the first museum retrospective of the artist since Sweet Oblivion: The Urban Landscape of Martin Wong at the New Museum in 1998, is accompanied by a no-less ambitious exhibition catalog.